2019
DOI: 10.3390/ijms20184548
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Mechanisms in Limb-Girdle Muscular Dystrophy with CAPN3 Mutations

Abstract: Limb-girdle muscular dystrophy recessive 1 (LGMDR1), previously known as LGMD2A, is a rare disease caused by mutations in the CAPN3 gene. It is characterized by progressive weakness of shoulder, pelvic, and proximal limb muscles that usually appears in children and young adults and results in loss of ambulation within 20 years after disease onset in most patients. The pathophysiological mechanisms involved in LGMDR1 remain mostly unknown, and to date, there is no effective treatment for this disease. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 151 publications
(229 reference statements)
3
23
0
Order By: Relevance
“…We also describe a group of people affected by calpainopathy (LGMD-R1), the most frequent form of girdle dystrophy, which in European countries would represent about 40–50% of total cases of LGMD [ 15 , 16 , 17 , 18 , 19 ], a recessive form, due to mutations in the gene coding for calpain-3 ( CAPN3 ), a muscle specific family’s member of Ca ++ activated neutral protease [ 20 ]. The identification of the disease locus in chromosome 15 [ 21 ], the first mutations in the CAPN3 gene were then identified both in France [ 22 ] and clinically described in a group of LGMD-R1 patients who lived in a small community [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also describe a group of people affected by calpainopathy (LGMD-R1), the most frequent form of girdle dystrophy, which in European countries would represent about 40–50% of total cases of LGMD [ 15 , 16 , 17 , 18 , 19 ], a recessive form, due to mutations in the gene coding for calpain-3 ( CAPN3 ), a muscle specific family’s member of Ca ++ activated neutral protease [ 20 ]. The identification of the disease locus in chromosome 15 [ 21 ], the first mutations in the CAPN3 gene were then identified both in France [ 22 ] and clinically described in a group of LGMD-R1 patients who lived in a small community [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CAPN3 missense variant p.(Asp707Gly) reportedly causes autosomal recessive inheritance, leading to severe and progressive clinical features and typical and evident muscular weakness and atrophies (11,36,37,39). Missense CAPN3 variants not only affect calpain 3 enzymatic activity, but also affect binding between protein molecules, thereby affecting protein integrity (20). Notably, previous studies showed that CAPN3 variants can also cause the autosomal dominant pattern of LGMDD4 and deletion variants c.643_663del21, c.598_612del15, as well as missense variant c.1333G>A (8,40,41) can trigger similarly mild clinical features in the case of LGMDR1.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that missense variants in CAPN3 are the most common type and frequently occur in the cysteine protease and PEF domain of calpain 3. The PEF domain binds four Ca 2+ ions per protomer through EF1, EF2, EF3 and EF5 and three Ca 2+ -binding EF-hands are concentrated near the protease core, which may facilitate calpain 3 homodimerization and calcium ion binding and radically alter the local charge within the dimer during Ca 2+ signaling (20,32). The two CAPN3 variants identified in the present study are respectively located in EF2 and EF3 of the PEF domain and may significantly change the 3D structure and disrupt the conformational stability of domain IV, thereby affecting the transmission of calcium signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-length form of CAPN3 is expressed mainly in skeletal muscle [8]. CAPN3 demonstrates its non-proteolytic activity by stabilizing Ca 2+ -handling proteins (CSQ [9], SERCA [10], RyR1 [11], CaMKII [11], and NCX3 [12]) and maintaining Ca 2+ homeostasis, which is extremely important and essential for muscle structure and function [5].…”
Section: Introductionmentioning
confidence: 99%